Northern forest tree populations are physiologically maladapted to drought - Miriam Isaac-Renton (Nature Portfolio, 2018)
Northern tree populations may not benefit under climate change, with implications for assisted migration and range expansion. Here, Isaac-Renton et al. show that leading-edge lodgepole pine populations have fewer characteristics of drought-tolerance, so may not adapt to tolerate drier conditions.